(untitled) (Dhaka University Journal of Biological Sciences, 2025)
Haor ecosystems of Bangladesh play significant roles in fisheries, aquatic biodiversity and on ecotourism along with other socio-economic activities of the area. So, knowledge on water quality and the structure of the grazing food chain to support fisheries production are highly important research issues. In this respect, Tanguar Haor of Sunamganj District and Hakaluki Haor of Moulvi Bazar District have already been studied. In the present research, the physicochemical and biological water quality parameters, including phytoplankton biomass and population density were studied in the Nikli Haor, Kishoreganj. Water and plankton samples from five stations (D1 - D5) were collected on June 27, 2022. The sampling was done on a 10 km stretch of haor water and 16 different variables were analyzed. Air temperatures ranged from 31.0 – 33.7°C, while water temperatures ranged from 30.40 – 31.40°C. Secchi depths ranged from 0.87 – 1.21 m and water depths of the studied stations ranged from 1.75 – 7.22 m. Of the chemical parameters pH and alkalinity varied from 7.9 – 8.3 and 0.65 – 0.92 meq/L, respectively. The concentration of dissolved oxygen (DO) and free-CO2 in the haor water ranged from 7.35 - 11.55 and 0.49 – 1.05 mg/L, respectively. The electrical conductivity (EC) and total dissolved solids (TDS) varied from 30.00 – 50.00 μS/cm and 34.00 – 42.00 mg/L, respectively. Among dissolved nutrients, the range of soluble reactive phosphorus (SRP) concentration was recorded as 6.7 - 45.6 μg/L, whilst soluble reactive silicate (SRS) varied from 6.10 – 11.20 mg/L. Values of NO3-N measured for the haor water ranged from 0.33 – 0.81 mg/L. Phytoplankton biomass as chl-a varied from 5.92 - 31.97 μg/L, its degraded product, phaeophytin concentration ranged from 1.60 - 3.31 μg/L. Among biological parameters, the phytoplankton density ranged from 10.40×106 – 17.50×106 ind./L across the 5 sampling sites. A total of 42 taxa of plankton were identified and presented with their images and systematic positions. Chlorophyta and Chrysophyta were the most dominant divisions of phytoplankton and yielded on total 10 and 11 taxa, respectively. Cyanophyta was represented by 6 taxa. Pyrrophyta was represented by 4 taxa. From zooplankton one rhizopod, two copepods and three rotifers populations were identified from the community. Considering the biological quality of plankton and the concentration of key nutrients the Nikli Haor water may be classified as meso- to eutrophic. Dhaka Univ. J. Biol. Sci. 34(2): 89-101, 2025 (July)